Factors influencing the pregnancy rate in indigenous ewes following AI using frozen semen (Bangladesh Veterinarian, 2018)
Study was conducted to observe the influence of different factors on pregnancy rate in 24 indigenous ewes following artificial insemination (AI) with frozen semen. The ewes were synchronized by intra-muscular injection of Prostaglandin F2α (Ovuprost® Bayer, New Zealand). The onset and intensity of oestrus were determined by oestrus behaviour of ewes with vasectomized ram. VER values were measured immediately before AI using electrical heat detector (DRAMINSKI®, Owocowa 17, Poland). Twelve ewes were inseminated trans-cervically and 12 laparoscopically. Five ewes were treated with Misoprostol (Cytomis® 200 µg tablet; Incepta Pharmaceuticals Ltd. Bangladesh) to relax the cervix 12 hours before TCAI, and cervical penetration depth was measured by a steel rod. Pregnancy was confirmed by ultrasonography at 40 – 45 days after AI. Cervical penetration depth was significantly increased (P